Management of pain in elite athletes: Identified gaps in knowledge and future research directions - Zideman, D. A.; Derman, W.; Hainline, B.; Moseley, G. L.; Orchard, J.; Pluim, B. M.; Siebert, C. H.; Turner, J. A. (Clinical Journal of Sport Medicine, 2018)
Objective: For elite athletes to train and compete at peak performance levels, it is necessary to manage their pain efficiently and effectively. A recent consensus meeting on the management of pain in elite athletes concluded that there are many gaps in the current knowledge and that further information and research is required. This article presents the crystallization of these acknowledged gaps in knowledge.